The role of chloroplast protein remodeling in stress responses and shaping of the plant peptidome. Issue 5 (18th May 2020) - Mamaeva, Anna; Taliansky, Michael; Filippova, Anna; Love, Andrew J.; Golub, Nina; Fesenko, Igor
Summary: In addition to photosynthesis, chloroplasts perform a variety of important cellular functions in the plant cell, which can, for example, regulate plant responses to abiotic and biotic stress conditions. Under stress, intensive chloroplast protein remodeling and degradation can occur, releasing large numbers of endogenous peptides. These protein‐derived peptides can be found intracellularly, but also in the plant secretome. Although the pathways of chloroplast protein degradation and the types of chloroplast proteases implicated in this process have received much attention, the role of the resulting peptides is less well understood. In this review we summarize the data on peptide generation processes during the remodeling of the chloroplast proteome under stress conditions and discuss the mechanisms leading to these changes. We also review the experimental evidence which supports the concept that peptides derived from chloroplast proteins can function as regulators of plant responses to (a)biotic stresses.